Physical abilities of community-dwelling adults more than six months post stroke: a cross sectional survey - Dearle, Luschka Anne (My University, 2010)
Background and purpose of the study The length of stay for patients with stroke in some South African government hospitals has been shown to be inadequate and there is little information on the physical impairments and functional abilities of this population once they return to the community. An assessment was done of the strength, range of movement and the presence of pain experienced by patients with stroke in the Daveyton community and the relationship between these impairments and the functional abilities of these patients was established. Research methods and procedures employed This was a quantitative study using a descriptive cross sectional study design. Thirty-four conveniently sampled patients with stroke were assessed in their Daveyton homes. The functional measures used were the Modified rivermead mobility index (MRMI) and Barthel index (BI). The strength was assessed using a hand-held dynamometer, range of movement (RoM) with a standard universal goniometer and pain with the Eleven faces pain scale. The significance of the study was set at 0.05 and the relationships between impairments and functional abilities were expressed using the Spearman’s rank correlation coefficient. Results Significant differences were found between the strength, as well as the RoM of the affected and unaffected sides (p < 0.05). The muscles most affected by were: Biceps, Gastrocnemius and Tibialis Anterior. The smallest strength difference was found in Gluteus maximus. The ranges of movement most affected were: shoulder flexion and elbow extension. The smallest difference was found in knee extension. Eighty-five percent of the sample attained scores indicating that they were independently mobile (measured by the MRMI), and 82% were independent in activities of daily living (measured by the BI). There were good correlations between the patients’ strength impairments and their functional abilities (r = 0.54 to 0.79) and mobility (r = 0.51 to 0.76). Functional abilities and mobility had moderate to good relationships with active range of movement of shoulder flexion, lateral shoulder rotation and dorsiflexion. The percentage of patients experiencing pain was 73%, but pain displayed no relationship with functional ability (r = 0.14) and mobility (r = 0.15). Conclusion Most people living with stroke in the Daveyton community are functionally independent despite the high prevalence of pain. Stroke results in significant strength and active range of movement deficits on the affected side. Most strength impairments correlated well with the functional ability and mobility of this sample, but active range of movement impairments that influenced functional measures were mainly shoulder and ankle movements.
MSc Physiotherapy, Faculty of Health Sciences, University of the Witwatersrand
Keywords: stroke; community; goniometer; dynamometer; impairments; function; mobility; strength; pain